Obraz autointerpretacji profesji lekarskiej – narracje lekarzy - Antoszewska, Beata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
This paper is an attempt to examine the senses and meanings attributed by physicians to the medical profession. The collected material is part of a larger project devoted to the physician-patient relationship reconstructed on the basis of individual narrations provided by physicians. The conducted research is closely linked to the qualitative perspective: Interpretative Paradigm and Interpretive Paradigm. The study was performed in the period 2015-2017. The examined group consisted of 16 subjects (6 female and 10 male physicians) from several provinces of Poland who were highly esteemed (subjective opinions) by their patients. The empirical data were collected by means of narrative interviews and the methodology applied for the analysis of the content was that of phenomenography.